Developing the theoretical model of Chinese physical education teachers’ health communication competence: based on grounded theory - Chen, Lilin; Xu, Yue; Li, Fangfei; Sun, Mingzhu; Yin, Zhihua; Guo, Zhen; Liu, Bo (Frontiers in Public Health, 2023)
1) Background: Physical education teachers' health communication competence is a key factor to health promotion. Although health communication is a multidisciplinary field, medical practitioners are the primary focus of health communication research, while physical education teachers are marginalized. Therefore, this study proposes a theoretical model of health communication competence for physical education teachers.(2) Methods: This qualitative research utilized interviews as the primary data collection method. Purposeful sampling was employed to select participants, including university teachers, primary and secondary school teachers, and health education professionals from diverse religions of China. The total of 31 participants were interviewed through two focus groups(N=15) and individual semi-structured interviews(N=16). Grounded theory was used to analyze and code the collected interview materials.(3) Results: The health communication competence of physical education teachers consists of three main categories, 10 subcategories, 30 concepts, and 240 statement labels. The three main categories are as follows: (i) foundations of health communication knowledge and skills. This category encompassed three subcategories, namely sport and health knowledge reserve, health beliefs, and health behaviors; (ii) health communication perception competence. This category includes two subcategories, namely health risk and crisis perception competence and communication audience perception competence: (iii) practical competence of health communication. It consists of five subcategories, namely language expression competence, organizational and design competence, utilization of new media tools competence, communication content selection and processing competence, and professional skills. (4) Conclusion: The theoretical model of health communication competence in this study provides a foundation for physical education teachers' involvement in health communication work. It can serve as a reference for the development of both pre-service health education courses and in-service training systems for physical education teachers. Future research can expand the sample size and geographic coverage to further validate the applicability of the findings. Additionally, investigate the factors influencing the formation of the identified competencies is recommended.